Подготовка научных библиотечных кадров в советском союзе - Владимиров, Лев (Knygotyra, 1974)
The problem of training scientists in librarianship has lately acquired additional importance. The more sophisticated needs of the age of scientifical-technical revolution require a qualitatively higher stage in the development of librarianship and therefore profound studies and revised definitions of its characteristic regularities and organizational forms. This new scientific approach to the problems of librarianship has to be implemented not only by scientists doing library research, but also, and in no less degree, by practical workers, organizers of library services. The organizers and engineers of library development at this new and complex stage should not only be experienced practical workers and administrators, but they should be able to study and solve all the emerging problems with the insight and methodical approach of a scientist. The principal form of training scientists and research personnel in the USSR is „aspirantura“ (post graduate studies). At present there are more than 100.000 aspirants, apart from the considerable guantity of specialists writing their thesises independently, without the „aspirantura“. A successful completion of aspirantura training (full time aspirantura duration – three years, and by correspondence – four rears) is crowned with the presentation and the defense of a candidate dissertation (thesis) which must show the applicant’s apritude for research. The degree of candidate of science is equivalent to the degree of doctor phil. in the USA. As to the doctoral dissertation, it must prepresent an independent research paper, containing theoretical analysis and conclusions and suggesting solutions of significance for the general development of the branch of science as well as for immediate practical application. The aspirantura to train scientific library personnel was first established in 1930 at the Leningrad N. Krupskaya political-educational Institute (now Institute of Culture). Later – in 1934 – at the Moscow Institute for Librarianship. According to the data presented by the All-Union Book Chamber, during the period of 25 years (1945–1970) in the field of bibliology only 11 dissertations have been granted the doctoral degree and 290 the degree of candidate of science. The majority of these dissertations deals with problems of traditional bibliology 50 treat problems of the history of book and printing, 77 – problems of bibliography, 101 – those of librarianship. Besides the Leningrad and Moscow Institutes of culture, a significant contribution to the training of scientists in the field of bibliology has been made by the Moscow Poligraphic Institute, the Moscow Historical-Archival Institute, the All-Union Institute of Scientific and Technical Information, some universities (Moscow, Vilnius, Tbilisi) etc. As to the topics of the dissertations we can witness a growing interest in the problems of information science, automation and mechanization of library work and similar actual topics. One of the main problems on which largely depends the training of scientific library personnel is the „doctoral“ problem, for the possibility to have as aspirantura at a certain research institute or establishment of higher education depends upon the number of doctors of science they possess. In the coming 2–3 years we can expect from 10 to 12 doctoral bibliological dissertations to be presented at the Leningrad and Moscow Institutes of Culture and the Vilnius university and elsewhere. This will make the conditions for the training of scientific library personnel even more favourable.